Bridging immunogenicity assays for IgG4 therapeutics: mitigating interference from Fc–Fc interactions. (May 2017) - Partridge, Michael A; Vijayam, Uma; Karayusuf, Elif Kabuloglu; Shum, Enoch; Sirimanne, Thanoja; Garlits, John; Chen, Jihua; Torri, Albert; Sumner, Giane
Aim : A bridging immunogenicity assay for a human IgG4 mAb therapeutic was transferred to an automation system to increase throughput. However, background signal increased five- to six-fold during the 6- to 8-h run.Results: Noncovalent Fc contacts formed between labeled IgG4 drugs in reagent solutions stored during the automation run. This generated substantial background signal, reducing assay sensitivity by approximately sixfold. Fc interactions also significantly impacted the confirmation assay. Fc contacts formed between labeled and unlabeled drug, significantly increasing signal inhibition (∼7–70%) in the 6-h run.Conclusion: Storing labeled antibody solutions separately and combining them immediately before adding to samples reduced interference from Fc interactions. Preincubation time for reagent solutions should be strictly controlled for anti-drug antibody assays with IgG4 drugs to avoid false-positive results.